Estudo das propriedades estruturais, optoeletrônicas, térmicas e vibracionais de MB4O7 (M= Si, Ge, Yb e Ce) via DFT e métodos experimentais - Santos, Willian Oliveira (2025)
Technological evolution in recent decades has brought notable advances in electronic devices, optoelectronics and renewable energy systems. Tetraborates, for instance, have attracted great interest within the scientific community due to their unique optoelectronic properties, standing out for their high transparency, wide band gap, intense luminescence, and remarkable stability, which make them promising candidates for applications in photonics, dosimetry, and light- emitting devices. In this work, we carried out a theoretical and experimental study to understand the properties of new, unprecedented tetraborates. The first part of this work was to carry out calculationsab initio, based on the density functional theory implemented CASTEP code, for theoretical understanding of crystalline systems of the MB4O7 type with (M= Si, Ge, Yb and Ce). We investigate structural, electronic, vibrational, thermodynamic and optical properties. As a result, it was seen that systems of the MB4O7 type with (M= Si, Ge, Yb and Ce) present insulating and direct and indirect gap semiconductor characteristics. Moreover, the mechanical stability, a crucial aspect assessed theoretically through the phonon spectrum, was confirmed by the absence of negative frequencies in the investigated structures. Through thermodynamic functions (enthalpy, entropy, free energy and thermal capacity) we have evidence of how the structure formation process occurs (free from impurity and with impurity).In the second part of this study, the experimental characterization of the GeB4O7 system was carried out. Thermal analysis (DTA/TG) revealed that the material has good thermal stability, while X-ray diffraction confirmed its well-defined crystalline structure, compatible with standards reported in the literature.